Diffusion and Interaction Dynamics of Individual Membrane Protein Complexes Confined in Micropatterned Polymer‐Supported Membranes. Issue 4 (26th October 2012) - Waichman, Sharon; Roder, Friedrich; Richter, Christian P.; Birkholz, Oliver; Piehler, Jacob
Abstract: Micropatterned polymer‐supported membranes (PSM) are established as a tool for confining the diffusion of transmembrane proteins for single molecule studies. To this end, a photochemical surface modification with hydrophobic tethers on a PEG polymer brush is implemented for capturing of lipid vesicles and subsequent fusion. Formation of contiguous membranes within micropatterns is confirmed by scanning force microscopy, fluorescence recovery after photobleaching (FRAP), and super‐resolved single‐molecule tracking and localization microscopy. Free diffusion of transmembrane proteins reconstituted into micropatterned PSM is demonstrated by FRAP and by single‐molecule tracking. By exploiting the confinement of diffusion within micropatterned PSM, the diffusion and interaction dynamics of individual transmembrane receptors are quantitatively resolved. Abstract : Micropatterned polymer‐supported membranes based on photochemical coupling of hydrophobic tethers are established as a platform for functional reconstitution of transmembrane proteins. Thus, lateral motion within the membrane is possible, but confined within micrometer dimensions, enabling the simultaneous probing of diffusion and interaction dynamics of individual membrane protein complexes in a quantitative manner.